Impact of person-job fit and person-organization fit on employee engagement: Moderating role of supervisor support - Alamgir Hossain; Mahfuja Khatun; Samia Shanjabin (Goodwood Publishing, 2023)
Purpose: This study aimed to examine the impact of two fit concepts, namely, Person-Job fit (P-J) and Person-Organization fit (P-O), on employee engagement while taking supervisor support as the moderating variable. Research Methodology: The relationships among constructs were analyzed using correlation, and the study hypotheses were tested using regression. All employees of different mobile telecommunication companies in Bangladesh comprised the study population. The sample size was 100, which was determined using the judgmental sampling technique. Primary data were collected from a field-level survey using a structured questionnaire. Results: The results revealed a positive association between employee engagement and person-job fit, whereas person-organization fit had a similar association with engagement. The impact of these variables on employee engagement ultimately affects turnover intention. This study also revealed that the association between person-organization fit and employee engagement was positively moderated by supervisor support. Conclusions: The study shows that person-job fit and person-organization fit positively impact employee engagement, with supervisor support moderating the P-O fit-engagement relationship and reducing turnover intention. Limitations: The study used a common non-probability sampling technique and a small sample size, which are a limitations. Contributions: The insights will help managers to ensure a match between the job and organizational requirements and those of employees. The study will also inspire future research to connect field theory and Social Exchange Theory (SET) with different concepts in different country and industry contexts. Novelty: For the first time in the relevant field, this study simultaneously connected field theory and SET theory with P-J and P-O fit regarding employee engagement.